2015
DOI: 10.1016/j.jpainsymman.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Clinician Communication About End-of-Life Care in Patients With Advanced Chronic Organ Failure During One Year

Abstract: End-of-life care communication is poor in patients with chronic organ failure and does not change toward the end of life. Future studies should develop an intervention aiming at initiating high-quality end-of-life care communication between patients with advanced chronic organ failure and their clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 42 publications
1
35
0
4
Order By: Relevance
“…17 out of 37 papers highlighted that a variable percentage of COPD patients had discussed palliative care topics, this ranged from 0% to 56%, [5,19,21,24,25,29,30,[35][36][37][38][39][40][41][42][43][44]. Within this group, the majority (n=9), reported rates of discussion ⩽30% of patients [19,29,30,[35][36][37][38][39]43]. This information was generated from papers including qualitative and quantitative studies with moderate and high quality, papers which compared COPD patients and patients with other diseases and narrative reviews.…”
Section: Frequency Of Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17 out of 37 papers highlighted that a variable percentage of COPD patients had discussed palliative care topics, this ranged from 0% to 56%, [5,19,21,24,25,29,30,[35][36][37][38][39][40][41][42][43][44]. Within this group, the majority (n=9), reported rates of discussion ⩽30% of patients [19,29,30,[35][36][37][38][39]43]. This information was generated from papers including qualitative and quantitative studies with moderate and high quality, papers which compared COPD patients and patients with other diseases and narrative reviews.…”
Section: Frequency Of Discussionmentioning
confidence: 99%
“…Several studies reported the most frequent and the least discussed topics during palliative care discussions, these are highlighted in table 3 [3,15,20,21,35,39,41,44,[46][47][48][51][52][53]. Overall, patient education about palliative care was ranked as one of the most important topics by patients with COPD [51].…”
Section: Content Of Discussionmentioning
confidence: 99%
See 3 more Smart Citations